Associations between depressive symptoms, activity of daily living, and falls/severe falls: evidence from two prospective longitudinal studies - Huang, Li; Jin, Wei; Liang, Zhenzhen; Chen, Huajian (Social psychiatry and psychiatric epidemiology, 2025)
Falls are the second leading cause of unintentional injury deaths globally and are strongly associated with a variety of psychological and physiological factors. Studies have suggested an association between depressive symptoms and fall risk, but the mechanism of action is unclear. This study aimed to investigate the association between depressive symptoms and the risk of falls and severe falls, and to examine whether activities of daily living (ADL) impairment mediates this relationship.
Gesehen am 23.10.2025